Manfaat Studi Biblika Kontekstual Dalam Kehidupan Iman Kristiani Di Era Distruptive - Agung Jaya (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
The distruptive era is a dil process where a product or service initially targets the bottom of the market (lower segments, bottom, low-end) and then moves to the top of the market (premium market) after it has finally eliminated the incumbents bailiff. The continued progress of human civilization and the increasing science brought man to the development t of the age even in specialized theological studies the biblika’s change ever took place. Our current big problem with studying the bible is that we think studying the bible should be so much easier than anything else that we think it is the only subject we don’t need to study. In this narrative the writer employed a qualitative method with studies of literature that utilize exixting resources such as books, and a trusted jurnal. Generally hermeneutic is the theoretical and methodological process of understanding the Max found in the signs and symbols used in both written and spoken communication. In doing a biblika study an interpreter will not be complete nudged until he moves from text to context (distruptiv). After the author elaborates hermeneutic contextually then the author arrived at the two benefits of Christian ethics vakni and contextual theology hermenenutic